Exposure to Antibiotics Induces Expression of the Mycobacterium tuberculosis sigF Gene: Implications for Chemotherapy against Mycobacterial Persistors - Michele, Theresa M. (American Society for Microbiology, 1999)
The sigF gene encodes an alternate sigma factor found in Mycobacterium tuberculosis and related pathogenic mycobacteria. Determination of conditions of sigF expression is an important step in understanding the conditional gene regulation which may govern such processes as virulence and dormancy in mycobacteria. We constructed an in-frame translational lacZ-kan fusion within the sigF gene to determine the conditions of sigF expression. This reporter construct was expressed from a multicopy plasmid in a strain of BCG harboring an integrated luciferase reporter gene under the control of the mycobacteriophage L5 gp71 promoter. Antibiotic exposure, in particular, ethambutol, rifampin, streptomycin, and cycloserine treatment, increased the level of SigF reporter specific expression in a dose-dependent fashion. The level of SigF reporter specific expression increased over 100-fold in late-stationary-phase growth compared to that in exponential growth. During the exponential phase, SigF specific expression could be induced by a number of other stresses. Anaerobic metabolism induced SigF by greater than 150-fold, particularly in the presence of metronidazole. Cold shock increased the level of SigF specific expression, while heat shock decreased it. Oxidative stress was also an important inducer of SigF specific expression; a greater induction was seen with cumene hydroperoxide than with hydrogen peroxide. Comparisons of bacterial viability as determined by the luciferase assay or by plating serial dilutions revealed that luciferase gp71-dependent activity was an unreliable predictor of the numbers of CFU during stationary-phase growth and anaerobic metabolism. The induction of sigF following antibiotic exposure suggests that this bacterial transcription factor may control genes which are important for mycobacterial persistence in the host during chemotherapy.